Morphoanatomy and physiology of Swietenia macrophylla in different light environments: Insights into its invasive ability in the Philippines - REGULOS NOLASCO AGOTO JR.; JONATHAN OGAYON HERNANDEZ; BYUNG BAE PARK (Society for Indonesian Biodiversity, 2024)
Abstract. Agoto Jr. RNA, Hernandez JO, Park BB. 2024. Morphoanatomy and physiology of Swietenia macrophylla in different light environments: Insights into its invasive ability in the Philippines. Biodiversitas 25: 257-263. Evidence supporting Swietenia macrophylla G.King's invasive ability is primarily inferential to date. The present study analyzed the variation in morphoanatomical and physiological traits of the species between shaded and sun-exposed environments to provide insights into its invasive ability in the Philippines. The variations in leaf area, seedling height, leaf pH, biomass, parenchyma and collenchyma cell thickness, lumen area of xylem vessels, stomatal conductance, and leaf relative water content were analyzed between shaded and sun-exposed light conditions. While stem and leaf biomass did not differ between the two light conditions, root biomass was 27% higher in the shaded than in the sun-exposed seedlings. Leaf pH was substantially lower in the shaded than in the sun-exposed condition. The vessel lumen area in both leaf and root was significantly larger in shaded than in sun-exposed condition by 10-15%. The parenchyma of seedlings in the shady area of the forest was thicker (c.a., 1-2 layers) compared to those in the well-lit environment, particularly in the leaf and root. While stomatal conductance was similar between the two light environments, shaded ones had a much larger leaf relative water content, up by 9-12%. Overall, we found significant morphoanatomical and physiological variations between shaded and sun-exposed seedlings, indicating invasive species' light-capture strategy and providing insights into S. macrophylla's invasive potential in the Philippines.